2022
DOI: 10.1186/s13018-022-03142-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of total knee arthroplasty on knee proprioception of patients with knee osteoarthritis: a meta-analysis

Abstract: Background Studies have given some pieces of evidence for the effect of total knee arthroplasty (TKA) on knee proprioception of patients with knee osteoarthritis (KOA), but their results were conflicting. This review was performed to provide an updated evidence-based meta-analysis investigating the influence of TKA on knee proprioception. Methods The electronic databases including PubMed, Google Scholar, and the Cochrane Library were accessed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Regarding the muscles around the knee, changes in the cross-sectional area and fatty degeneration of the knee muscles due to arthritis have been reported [48]. Additionally, decreased knee proprioceptive capacity will have an effect on the limits of stability in KOA individuals [13], since reduced proprioceptive afferent input to higher centers will modify the peripheral motor output, resulting in impaired somatomotor control [49]. Sanchez-Ramirez et al [50] showed that postural control is altered and proprioceptive accuracy is impaired in 284 KOA individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the muscles around the knee, changes in the cross-sectional area and fatty degeneration of the knee muscles due to arthritis have been reported [48]. Additionally, decreased knee proprioceptive capacity will have an effect on the limits of stability in KOA individuals [13], since reduced proprioceptive afferent input to higher centers will modify the peripheral motor output, resulting in impaired somatomotor control [49]. Sanchez-Ramirez et al [50] showed that postural control is altered and proprioceptive accuracy is impaired in 284 KOA individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors have demonstrated increased knee joint positioning errors (JPE) in KOA individuals compared to age-matched asymptomatic individuals [9][10][11][12]. Different factors, such as degeneration, decreased muscle strength, and endurance, impair mechanoreceptor function, and thereby affect afferent proprioceptive input to the higher centers, resulting in altered motor output and proprioceptive function [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of surgical treatment may be influenced by factors such as pain, joint function, anatomical factors and patient's physical function (152). Current surgical treatment methods for KOA include knee arthroscopy (153), bone marrow stimulation (154) and osteotomy (155)(156)(157) and joint replacement (158), fusion (159) and arthroplasty (160). For patients with early-to-mid-stage KOA, joint arthroscopy is a better option as it provides the advantages of a smaller wound and rapid recovery (153).…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Researchers have notably underscored the importance of assessing proprioception, particularly within patient cohorts like those with OA, given its strong correlation with knee functional performance [65]. Generally, a trend toward enhanced proprioception levels post-TKA is recognized [65,66]. Nevertheless, some studies report no significant difference in proprioception levels between the preoperative and postoperative phases [67,68].…”
Section: Discussionmentioning
confidence: 99%